How climate, topography, soils, herbivores, and fire control forest–grassland coexistence in the Eurasian forest‐steppe. (9th August 2022) - Erdős, László; Török, Péter; Veldman, Joseph W.; Bátori, Zoltán; Bede‐Fazekas, Ákos; Magnes, Martin; Kröel‐Dulay, György; Tölgyesi, Csaba
ABSTRACT: Recent advances in ecology and biogeography demonstrate the importance of fire and large herbivores – and challenge the primacy of climate – to our understanding of the distribution, stability, and antiquity of forests and grasslands. Among grassland ecologists, particularly those working in savannas of the seasonally dry tropics, an emerging fire–herbivore paradigm is generally accepted to explain grass dominance in climates and on soils that would otherwise permit development of closed‐canopy forests. By contrast, adherents of the climate–soil paradigm, particularly foresters working in the humid tropics or temperate latitudes, tend to view fire and herbivores as disturbances, often human‐caused, which damage forests and reset succession. Towards integration of these two paradigms, we developed a series of conceptual models to explain the existence of an extensive temperate forest–grassland mosaic that occurs within a 4.7 million km 2 belt spanning from central Europe through eastern Asia. The Eurasian forest‐steppe is reminiscent of many regions globally where forests and grasslands occur side‐by‐side with stark boundaries. Our conceptual models illustrate that if mean climate was the only factor, forests should dominate in humid continental regions and grasslands should prevail in semi‐arid regions, but that extensive mosaics would not occur. By contrast, conceptual models that also integrate climate variability, soils, topography, herbivores, and fire depict how these factors collectively expand suitable conditions for forests and grasslands, such that grasslands may occur in more humid regions and forests in more arid regions than predicted by mean climate alone. Furthermore, boundaries between forests and grasslands are reinforced by vegetation–fire, vegetation–herbivore, and vegetation–microclimate feedbacks, which limit tree establishment in grasslands and promote tree survival in forests. Such feedbacks suggest that forests and grasslands of the Eurasian forest‐steppe are governed by ecological dynamics that are similar to those hypothesised to maintain boundaries between tropical forests and savannas. Unfortunately, the grasslands of the Eurasian forest‐steppe are sometimes misinterpreted as deforested or otherwise degraded vegetation. In fact, the grasslands of this region provide valuable ecosystem services, support a high diversity of plants and animals, and offer critical habitat for endangered large herbivores. We suggest that a better understanding of the fundamental ecological controls that permit forest–grassland coexistence could help us prioritise conservation and restoration of the Eurasian forest‐steppe for biodiversity, climate adaptation, and pastoral livelihoods. Currently, these goals are being undermined by tree‐planting campaigns that view the open grasslands as opportunities for afforestation. Improved understanding of the interactive roles of climate variability, soils, topography, fire, and herbivores will help scientists and policymakers recognise the antiquity of the grasslands of the Eurasian forest‐steppe.